(untitled) (Indian Journal of Arid Horticulture, 2025)
The surface sterilization is the most important step prior to initiate tissue culture and can become a critical point in establishment of certain species particularly when the explants was derived from field grown woody perennial plants. Kinnow mandarin (Citrus deliciosa) is a cross, between the king sweet orange (Citrus nobilis) and Willow leaf mandarin (C: deliciosa) developed in California by H.B. Frost. Kinnow fruits have a great therapeutic value due to favourable ratio of K and Na. Kinnow fruits are not only delicious and refreshing but also possess great nutritive value. It contains 10-12% carbohydrate, 0.6-0.8% protein, 0.9-1.1% vitamin A, 0.45-0.55% vitamin C, 0.01- 0.02% thiamine, 0.002 -0.003% riboflavin, 0.25-0.35% calcium, 0.18-0.25% magnesium and 0.028-0.034% iron.